Diagnóstico de gestão em cooperativas da agricultura familiar no Estado do Paraná: limites e potencialidades em um modelo solidário e democrático - Gregolin, Marcos Roberto Pires (2015)
The family farms cooperatives appear in actual scenery as a great model to sustainable development. They constitute solidary, democratic and participative enterprises which the family farmers can lead the ways of organization. The complexity of a conventional enterprise management is considerable, but of a solidary one is generally higher due the diversity of interests of each member and their triple expectation, being in the cooperative, in the same time, costumer, owner and supplier. This scenery is aggravated by the fact that in this kind of cooperative, the members need to dedicate themselves to the production in their properties and also to management of enterprise. Although is known the importance of management to efficiency of cooperative enterprises, it is small the knowledge about practices used to this management and about the difficulties and potentials of the practice in this segment. Thus, this study aimed to diagnose the practices in management of cooperatives of family farms from Paraná state, besides know the main difficulties and potentials relating the management practices, allowing offer a state panorama of cooperative management. Twenty five cooperatives that are served by the program Mais Gestão , from Agrarian Development Ministry (MDA) were studied. The research have a documental evidence and was realized having base in the diagnosis and Strategic Identification Matrix of each cooperative and analyzed their performance divided in six management areas: Organizational Management; Human Resource Management; Finances and Costs; Commercialization and Marketing; Industrial Management and Environmental Management. Each one of these areas was divided in subareas, totaling thirty, composed by multiple choice questions, totaling two hundred and sixty. The questions were answered considering the opinion of family farmers that compose the cooperative direction.With the study, it was clear that the cooperatives have greater difficulties in Organizational Management, since that 76% of the sample, the subarea organizational structure has a poor performance. In other areas and their respective subareas as Personnel Management (Education and training, 52%; and human resource indicators, 60%), Finances and Costs (costs indicators, 56%) and Environmental Management (Environmental Regulations, 52%), it was observed an unsatisfactory performance, however, the Organizational Management area still is the worst. It could be concluded that family farms cooperatives studied need a greater support and incentive at organizational management area, without disregard the support in other areas. The participation of the members in the enterprise management can improve their relation with the market, financial control, the human resource management and any demand of management, so, the improvement of organizational management can constitute a strategic differential and helping in the consolidation of family farms cooperatives with solidary intention